2008
DOI: 10.1177/0883073808319078
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Carcinoma Presenting with Multiple Metastases: Case Report

Abstract: Pituitary carcinoma, an uncommon tumor in adults, generally presents with craniospinal and systemic metastases. We report a case of pituitary carcinoma with multiple craniospinal metastases in a child. A 9-year-old girl, who had had a ventriculoperitoneal shunt operation 3 years ago, presented with complaints of progressive visual disturbance, headache, speech difficulty, and gait disturbance for the past 2 months. Neurological examination revealed papilledema, visual loss, and dysarthria. Cranial magnetic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…Takeshita el al [40] intend to continue tri-monthly maintenance therapy of a Crooke cell carcinoma after 2 years of sustained response to temozolomide in both the primary tumor and liver metastases. Guzel et al reported a presumed case of a 9-year-old girl with a null cell carcinoma unresponsive to temozolomide who died after 2 months [3]. We excluded the latter case from the list of bona fide reported tumors in that (a) the primary tumor did not originally affect the sella, (b) S-100 protein staining was noted, (c) no pituitary hormone immunostaining was noted in an age group [8,14,35,41,42] wherein almost all [8,14,35,[41][42][43] (Table 2).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Takeshita el al [40] intend to continue tri-monthly maintenance therapy of a Crooke cell carcinoma after 2 years of sustained response to temozolomide in both the primary tumor and liver metastases. Guzel et al reported a presumed case of a 9-year-old girl with a null cell carcinoma unresponsive to temozolomide who died after 2 months [3]. We excluded the latter case from the list of bona fide reported tumors in that (a) the primary tumor did not originally affect the sella, (b) S-100 protein staining was noted, (c) no pituitary hormone immunostaining was noted in an age group [8,14,35,41,42] wherein almost all [8,14,35,[41][42][43] (Table 2).…”
Section: Discussionmentioning
confidence: 97%
“…Representing 0.2% of all pituitary neoplasms, fewer than 150 cases are reported in the English literature [1][2][3][4][5][6][7][8][9][10][11]. Their local invasiveness about vital structures and, by definition, craniospinal axis or systemic metastasis, represents diagnostic and therapeutic challenges [12].…”
Section: Introductionmentioning
confidence: 99%
“…Although assessment of proliferation may be helpful in arousing suspicion as to subsequent tumor invasiveness and/or malignant potential, growth rate is probably not the only major determinant of tumor behavior and carcinogenesis. [1241415]…”
Section: Discussionmentioning
confidence: 99%
“…[11] Although histologically “atypical PAs” do not necessarily behave clinically as “atypical”, a high index of suspicion for these lesions is currently recommended. [13815] It was also noted that there does not seem to be a significant correlation between Ki- 67 LI and tumor size of PA, even if this index is considered as a useful marker in the determination of the infiltrative behavior of these tumors. [11] Clinically, the name “atypical pituitary adenoma” is used to describe tumors that recur or progress despite resection and radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…These tumours were null cell (n = 1) and Crooke cell carcinoma (n = 1) with multiple liver, intracranial and intraspinal metastases leading to patient death despite multiple treatments (169,174).…”
Section: Special Circumstances a Paediatricmentioning
confidence: 99%